(Y-5)=3(x-5)

Simple and best practice solution for (Y-5)=3(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (Y-5)=3(x-5) equation:



(-5)=3(Y-5)
We move all terms to the left:
(-5)-(3(Y-5))=0
We add all the numbers together, and all the variables
-(3(Y-5))-5=0
We calculate terms in parentheses: -(3(Y-5)), so:
3(Y-5)
We multiply parentheses
3Y-15
Back to the equation:
-(3Y-15)
We get rid of parentheses
-3Y+15-5=0
We add all the numbers together, and all the variables
-3Y+10=0
We move all terms containing Y to the left, all other terms to the right
-3Y=-10
Y=-10/-3
Y=3+1/3

See similar equations:

| 0.11x=-0.66. | | (2w+1)•w=66 | | 1x+45=30 | | 9x+17+6x+13=180 | | x^2-13x-25=0 | | 6x+7+5x+8=180 | | 1/7(14x)^1/3=1 | | 3x+5+2x+5=90 | | 0.4x+1.2=–0.2x | | 9x+39=138 | | d×14/19=1 | | 10.4=12.46=z | | 3x×4x-1x=1067 | | 81+8x=55+10x | | 36+45y-6y=21 | | 16-|x|=18 | | 2×+6y=13 | | 11^3x+24=11^15 | | 8/2(2/3)=7/x | | G(x)=-x^2-4x-1 | | 3(2x-5)-4=2x+9 | | 4x+3+4x+7=90 | | 2b^2+4b-16=0 | | F(-6)=x^2-x-2 | | 3(2x+6)=8x+9-2x+9 | | 50=10-10v | | 50=10-10b | | 2x=180-(6x+2x) | | 4x−2​(x−5​)=−3+5x | | 13m=5m | | c8 = 9 | | 9^x+3=2187 |

Equations solver categories